COMPENSATORY STRATEGIES OF FIRST-LANGUAGE-ATTRITED CHILDREN - Syahdan Syahdan (TEFLIN Journal: A publication on the teaching and learning of English, 2012)
This article explores the compensatory strategies used by two Indonesian children who experienced first language attrition when acquiring English in the English-speaking environment. They use compensatory strategies to compensate for their lack of competence in first language. They employ both interlingual strategies and discourse strategies when they have difficulties in communication. Interlingual strategies used are codeswitching and lexical borrowings and the discourse strategies are overt comments, appeal for assistance, and avoidance.